Development of educational complex on electrical engineering, electronics and microcon-trollers on modeling in TINA software - Vladimir A. Alekhin (Открытое образование (Москва), 2018)
The study of electrical engineering, electronics and microcontrollers in accordance with federal state educational standards requires from students the practical mastering of experimental methods for the study of electrical circuits and electronic circuits, the formation of competences and skills in the calculation of electrical circuits and electronic circuits. The modern development of information educational technologies, the widespread use of a variety of computer facilities by students in reducing teaching hours for the study of disciplines make it necessary to create new multimedia training complexes, using computer simulation of electrical circuits, electronic circuits and microcontrollers in the lecture process and in the laboratory and practical exercises. The purpose of the research was a comparative analysis of various computer simulation programs in terms of their accessibility, ease of development and efficiency of use by lecturers and students in the educational process, and the creation and testing of a training complex for the electrical engineering, electronics and microcontrollers using the selected modeling environment.The problems associated with the need to purchase licensed software were discussed and a comparative analysis of the following computer modeling programs for electrical circuits and electronic circuits was performed: NI Multisim, Micro-Cap, Proteus VSM, OrCAD, TINA. The research method included the study of these modeling and design programs, writing of teaching aids and conducting of training sessions with students. The cost of licenses for the software application in computer classes and on students’ home computers was estimated. As a result, the conclusion was confirmed about the advisability of using the free student program of computer modeling TINA-TI and the TINACloud environment from DesignSoft for the teaching of electrical engineering and electronics.The new software product TINACloud uses cloud-based Internet technologies and can be launched through the browser anywhere in the world without installing a program in the computer. This service offers many educational resources and allows students to carry out virtual research and laboratory practical work on electrical equipment, electronics and microprocessor technology on laptops, tablets and other mobile devices at any time and in any place. The cost of an annual student license is 12 Euros.With the use of TINA and TINACloud programs, a training complex on electrical engineering, electronics and microcontrollers was developed. It contains five published training manuals, electronic lecture notes on electrical engineering and electronics, computer labs on electrical engineering, electronics and microcontrollers, a multimedia workshop on electronics, video tutorials.This complex is being successfully used in the educational process for full-time and distance education, it also implements the concepts of modern open and mobile education, the basic materials of the complex are placed on the Internet on the website “Electrical engineering and electronics. Educational resources for students and teachers” [URL: http://www.toe-mirea.ru/].The educational complex can be used in universities and colleges to teach students in areas related to electronics, instrument engineering, and management in technical systems, robotics, radio engineering, computer science and computer technology, etc.